Emotional Support among the Aged People in Baghdad - Abdulrhman, Asmahan; Hamly, Rahim (Al-Adab Journal, 2023)
The emotional support is one of the important topics of humanity, provided by the social network of attention, sympathy, acceptance and sympathy to the individual, and the aged people in the care homes are the most urgently in need for emotional support due to the biological and psychological changes associated with age, and because of their distance from their social environment The current research aims to recognize emotional support of aged people in Care Homes, identify the difference in the emotional support components depending on the need for support, the search for support, the support received, and the difference in emotional support depending on the sex variable. researcher relied on the scale (Schwarzer & Schulz, 2000) for emotional support and the scale includes (22) items distributed on four sub-measures, the size of the research sample is (150) male and female aged people in governmental and civil Care Homes in Baghdad province. The results showed the following: 1- Aged people living in Care Homes have a level higher than the average level of emotional support. 2- There is a significant difference between the components of emotional support where the need for support has been shown higher than the search for support and showed higher perceived support than the support received and the need for support is higher than the support received. 3- There is no difference in emotional support in aged persons depending on the sex variable. In the light of the results of the current study, the researcher recommended a set of recommendations and suggestions, including: the Ministry of Labor and Social Affairs is asked to prepare and train care professionals to provide emotional support to the aged people in Care Homes.